청소년 참여 유형에 따른 임파워먼트 실천사례 연구 -진주지역 청소년 조직을 중심으로 - 김경호; Kyoung Ho Kim; 문지영; Ji Young Moon (청소년복지연구, 2005)
This study aimed to identify the contents of empowerment, which experienced by youth. Especially, the research on two case - youth development agency and youth action group - addresses as youth’s pattern of participation. In order to obtain these answers, this study employed an exploratory-descriptive research design. This design was primarily executed through semi-structured interview guide. The results of this study are as follows: 1) Youth action group empowerment consists in youth being conscious of their rights, and the youth rights can only continue to be kept by institutional environment formed by right-consciousness. On the other hand, having structures and programs that most allow youth to make decisions of their own as independently as possible, youth development agency leads youth to participate in the programs and to put their own skills to good use. 2) In the course of organization participation, youth experienced value change, increasing relationship, and social·political consciousness change. Especially, the continual participation was reinforced through practical activity. 3) Both organization - youth development agency and youth action group - can be properly combined into advisable ways to promote the empowerment of youth. Each of these two organization has merits of its own, so is supplementary to each other. KCI Citation Count: 3